BIODIESEL PRODUCTION FROM PALM OIL OVER SYNTHESIZED CERIA NANOMATERIALS - OLUWASEGUN, OYENUBI ABA YOMI (2017)
Many high yielding catalyst rangmg from homogenous, heterogeneous and biocatalysts have been used for biodiesel production. However, high amount of energy is still required to mix the reactants (oils and alcohols) during reactions. Therefore, this study examine four ceria nanomaterials that are capable of increasing miscibility by lowering the surface tension at the interface of the reactants.